2016
DOI: 10.1016/j.kint.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in acute kidney injury

Abstract: Autophagy is a conserved multistep pathway that degrades and recycles damaged organelles and macromolecules to maintain intracellular homeostasis. The autophagy pathway is upregulated under stress conditions including cell starvation, hypoxia, nutrient and growth-factor deprivation, ER stress, and oxidant injury, most of which are involved in the pathogenesis of acute kidney injury (AKI). Recent studies demonstrate that basal autophagy in the kidney is vital for the normal homeostasis of the proximal tubules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
263
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(275 citation statements)
references
References 193 publications
(238 reference statements)
8
263
2
2
Order By: Relevance
“…Mitophagy, one type of autophagy, is known as selective removal of damaged and depolarized mitochondria. Although initially identified in familial Parkinson’s disease [40], recent studies showed that autophagy in kidney was of great significance for the homeostasis of renal tubular [41, 42]. Autophagy and mitophagy have been well studied in renal ischemia-reperfusion, sepsis and cisplatin induced acute kidney injury [15, 43-45].…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy, one type of autophagy, is known as selective removal of damaged and depolarized mitochondria. Although initially identified in familial Parkinson’s disease [40], recent studies showed that autophagy in kidney was of great significance for the homeostasis of renal tubular [41, 42]. Autophagy and mitophagy have been well studied in renal ischemia-reperfusion, sepsis and cisplatin induced acute kidney injury [15, 43-45].…”
Section: Discussionmentioning
confidence: 99%
“…36,[190][191][192][193][194][195][196][197][198][199][200][201][202][203] An in-depth review of the relationship between autophagy and AKI has been published in this journal. 204 Autophagy in renal fibrosis. Unilateral ureteral obstruction (UUO) in rodents has been established as a classic model of progressive renal fibrosis.…”
Section: Autophagy In the Tubulointerstitial Compartmentmentioning
confidence: 99%
“…Growing evidence suggests that autophagy is involved in physiological processes as well as in pathogenesis of many kidney diseases [8, 9]. Autophagy is a highly conservative regulatory system in which intracellular damaged organelles and protein aggregates are removed via the lysosomal degradation pathway [10, 11].…”
Section: Introductionmentioning
confidence: 99%